Metaphors in Adele's Song Lyrics: A Linguistic Perspective - Olga Grace Sumolang (Arkus, 2021)
Metaphor is one of the figurative languages that takes two different things by identifying one with another. By using metaphor, it helps speakers or writers to give a clear description through comparison or contrast. Music is the attribute of sound in every background of human. To investigate the form and the meaning of metaphor found in the lyrics of the songs of Adele aims at the readers, especially the students of English Literature Major to use lyrics of the songs as a media in studying meaning. The method which is used in this research is descriptive method. In collecting data, the writer focused on identifying the words, phrases or noun. The result shows in terms of the identified metaphors, the writer found that the lyrics of the songs can be categorized as metaphor nominative subjective, metaphor nominative objective, metaphor predicative and metaphor sentence. The parts of sentences identified as metaphors are analyzed based on Lakoff is theory about tenor and source. Tenor refers to the underlying idea or principal subject of metaphor while source conveys the underlying; the borrowed idea, or the thing that has been resembled. The result of this study shows that the metaphor contains a certain meaning based on the context and each of them refers to a certain object of tenor and source.